The Securitization of a Despot: How the Bush Administration securitized Saddam Hussein - Sandhu, Jaswinder (Université d'Ottawa | University of Ottawa, 2013)
This paper applies securitization theory to the Bush administration‟s invasion of Iraq and the removal of its president, Saddam Hussein. First, it examines securitization theory in the field of international relations, and then applies the components of securitization to the Bush administration‟s actions leading up to the war in Iraq and in particular the capture of Saddam Hussein. Those three main components are the securitization actor, a securitization act (speech act), and the audience. In our case study, the Bush administration is considered the actor; the speeches delivered by President Bush and his administration regarding Saddam Hussein and his potential threat level to the US form the speech act and the audience is the American public, which ultimately had to accept the speech acts in order for the securitization to occur. The acts were aided by US media outlets, such as the New York Times and created headlines that reflected the view of the US government, which in turn impacted the audience in order to try to garner support. The speech acts given by the Bush administration and news stories created by the New York Times were powerful enough that securitization was able to occur and was accepted by the audience even though the Bush administration lacked evidence that Saddam Hussein had weapons of mass destruction.